2008
DOI: 10.1097/gco.0b013e3282f73253
|View full text |Cite
|
Sign up to set email alerts
|

Screening for fetal abnormalities with ultrasound

Abstract: Screening for fetal abnormalities continues to evolve with the introduction of novel techniques and the further refinement of previously proposed screening tools. How these modalities are implemented into routine clinical practice remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Doppler studies of the fetal circulation have demonstrated the importance of the DV in the continuous monitoring of fetuses with intrauterine growth restriction due to placental insufficiency, with some reports demonstrating an association of abnormal DV flow patterns and fetal chromosomal abnormalities, congenital cardiac defects, or adverse pregnancy outcome in highrisk pregnancies where increased values of the pulsatility index for veins (PIV) and absent or reversed flow during atrial contraction were related to abnormal pregnancy outcome [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Doppler studies of the fetal circulation have demonstrated the importance of the DV in the continuous monitoring of fetuses with intrauterine growth restriction due to placental insufficiency, with some reports demonstrating an association of abnormal DV flow patterns and fetal chromosomal abnormalities, congenital cardiac defects, or adverse pregnancy outcome in highrisk pregnancies where increased values of the pulsatility index for veins (PIV) and absent or reversed flow during atrial contraction were related to abnormal pregnancy outcome [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The overall sensitivity increases to 93% when first and second trimester ultrasound examinations are combined. 13 Detection of structural anomalies within the gestational period makes it possible to plan interventions during pregnancy or during the immediate and early postpartum period, thereby reducing perinatal and infant morbidity and mortality. 14,15 In addition, early detection facilitates multidisciplinary planning for maternal-fetal interventions that may be required during the gestational period and provides greater information for parents and relatives.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,10,14,31,32 This additional utility increases the clinical interest of the DV assessment. More research is needed to quantify the benefit of measuring DV flow in routine obstetric practice.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, several studies have demonstrated an increased impedance to flow in the ductus venosus at the 11 to 13 +6 weeks' scan in DS fetuses. [5][6][7][8][9][10][11][12] Therefore, ductus venosus (DV) Doppler studies could be used to modify the estimated DS risk either selectively in women referred because high-risk for this condition as a secondary screening method, [5][6][7]11,[13][14][15] or incorporated routinely into existing screening protocols as a primary screening method.…”
Section: Introductionmentioning
confidence: 99%